2019
DOI: 10.1038/s41598-019-43278-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Plasma Markers and Essential Hypertension in Middle-aged and Elderly Chinese Population: A Community Based Cross-sectional Study

Abstract: Plasma markers have been continuously advocated as pointers to estimate the long-term risk of cardiovascular disease in the general population. We examined the relationship between plasma high-sensitivity C-reactive protein (hs-CRP), homocysteine (Hcy), high-sensitivity cardiac troponin T (hs-cTnT), N-terminal prohormone of brain natriuretic peptide (NT-proBNP), 25-Hydroxyvitamin D (25OHD), glycosylated hemoglobin A1c (HbA1c), and serum uric acid (SUA) levels and hypertension in middle and old aged population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…These investigations were published between 2005 and 2020. A total of 59 of the investigations had a cross-sectional design ( 13 19 , 26 38 , 41 43 , 45 , 47 50 , 52 56 , 60 75 , 77 86 ), one investigation was a nested case–control ( 12 ), and 10 others were cohorts ( 39 , 40 , 44 , 46 , 51 , 57 – 59 , 76 , 87 ). One of these cohorts ( 46 ) had reported the association in both baseline and follow-up; so, it was included in the analysis of both cross-sectional and cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…These investigations were published between 2005 and 2020. A total of 59 of the investigations had a cross-sectional design ( 13 19 , 26 38 , 41 43 , 45 , 47 50 , 52 56 , 60 75 , 77 86 ), one investigation was a nested case–control ( 12 ), and 10 others were cohorts ( 39 , 40 , 44 , 46 , 51 , 57 – 59 , 76 , 87 ). One of these cohorts ( 46 ) had reported the association in both baseline and follow-up; so, it was included in the analysis of both cross-sectional and cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, when grouping HbA1c by quintiles, the above significant association was eliminated after normalizing for BMI. Moreover, elevated HbA1c levels dramatically aggravated the risk of hypertension in an independent manner even after normalizing traditional risk factors in general middle-aged and elderly Chinese subjects [38]. Besides that, the Framingham Heart Study demonstrated that high HbA1c expression was associated with the prevalence of hypertension, but it was only based on a univariate analysis [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, when grouping HbA1c by quintiles, the above significant association was eliminated after normalizing for BMI. Moreover, elevated HbA1c levels dramatically aggravated the risk of hypertension in an independent manner even after normalizing traditional risk factors in general middle-aged and elderly Chinese subjects [39]. Besides that, the Framingham Heart Study demonstrated that high HbA1c expression was associated with the prevalence of hypertension, but it was only based on a univariate analysis [40].…”
Section: Discussionmentioning
confidence: 99%